France-Brazil Cross-border Cooperation Strategies: Experiences and Perspectives on Migration and Trade. Issue 3 (3rd July 2017) - Silva, Gutemberg de Vilhena
ABSTRACT: This article analyzes the Cross-border cooperation (CBC) strategies between France and Brazil, highlighting two main issues: migration and trade. The questions that guided the study are: (1) what are the uses of the Franco-Brazilian border by the means of CBC initiatives-actions-programs in relation to migration and trade? and (2) what are the main barriers that compromise the development of the CBC in the studied area? The methodology of the study was comprised of: (a) bibliographic research; (b) documental research; and (c) field work. The data allowed an evaluation of the experimentations and expectations provoked by the CBC since the 1990s. A series of new strategic uses of the border were observed as a result of binational meetings, cooperation proposals and, in a smaller scale, concrete actions in the last 20 years. Debates and effective actions, such as the combat of the illegal migration to French Guiana, regarding migration, and the formulation of institutional mechanisms for commercial cooperation on the Franco-Brazilian border are examples of the initial attempts of cooperation between Brazil and France within the geographical space they physically share.